PTH-160 Laparoscopic repair of giant hiatus hernia significantly improves quality of life – a single centre experience. (22nd June 2015) - Goh, YM; Goh, YL; Krishnamohan, N; Shetty, VD; Turner, PD; Ward, JB; Pursnani, KG; Date, RS
Abstract : Introduction: Centralisation of Upper Gastrointestinal cancer services has been associated with increase in number of referrals of giant hiatus hernia (GHH) over last 5 years. Laparoscopic repair (LR) of GHH is associated with recurrence rate of up to 30% and high mortality and morbidity. Therefore, we offer surgery only to symptomatic patients presenting with reflux, dysphagia, chest symptoms and intermittent gastric volvulus. The aim of this study is to evaluate quality of life (QoL) of these patients after LR of GHH. Method: This is a postal questionnaire study of all the patients undergoing GHH repair between 2010 to 2014 in a tertiary referral centre. Patients were sent 2 questionnaires, 1. The Quality of Life in Reflux and Dyspepsia (QOLRAD) and 2. Our own short questionnaire. The QOLRAD questionnaire was made up of 25 questions; each scored out of 7 with 7 representing a high quality of life and 1 representing a low quality of life. A combination of these questions made up 5 dimensions namely emotional distress, sleep disturbance, food/drink problems, physical/social functioning and vitality. The second questionnaire assessed improvement in patient's individual symptoms namely heartburn/reflux, weight loss, abdominal or chest pain/discomfort, vomiting, shortness of breath, nausea, bloating, difficulty swallowing and also overall improvement in health and QoL on a scale of 0 to 10, 0 being no improvement and 10 being excellent results. Results: From a total of 68 patients, 2 died post-operatively (1 was an emergency and the other was an elective case). The other 2 died of unrelated causes. Of the remaining 64 patients, 27 (42.2%) responded. Mean score for each dimension in QOLRAD (out of 7) were as follows-emotional distress (6.15), sleep disturbance (6.22), food/drink problems (6.07), physical/social functioning (6.43) and vitality (6.02). In the second questionnaire, patients scored overall improvement of their symptoms out of 10. Of the 27 patients, 1 (3.7%) scored 1–3, 5 (18.5%) scored 4–6, 3 (11.1%) scored 7–8 and 18 (66.7%) scored 9–10. Similar findings were reported for improvement in QoL. Conclusion: Our case series showed acceptable operative mortality of 2.9%; with a significant improvement in QoL in approximately two thirds of patients. Patient selection and standardisation of operation may be responsible for these results. Disclosure of interest: None Declared.